2015
DOI: 10.1016/j.clinthera.2015.05.143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute Cardiovascular effects of immediate-release Methylphenidate in children and adolescents with attention deficit Hyperactivity disorder

Abstract: Attention-deficit hyperactivity disorder is a frequent condition in children and often extends into adulthood. Use of immediate-release methylphenidate (MPH) has raised concerns about potential cardiovascular adverse effects within a few hours after administration. This study was carried out to investigate acute effects of MPH on electrocardiogram (ECG) in a pediatric population. A total of 54 consecutive patients with attention-deficit hyperactivity disorder (51 males and 3 females; mean age =12.14±2.6 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Cardiovascular adverse effects of MPH had been a concern since it was first reported in 1958 [48]. MPH had a sympathomimetic property which could activate beta-adrenoreceptor on cardiac tissues [49]. However, elevated heart rate is a risk for major cardiovascular disease, and all of which could lead to death [50].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular adverse effects of MPH had been a concern since it was first reported in 1958 [48]. MPH had a sympathomimetic property which could activate beta-adrenoreceptor on cardiac tissues [49]. However, elevated heart rate is a risk for major cardiovascular disease, and all of which could lead to death [50].…”
Section: Discussionmentioning
confidence: 99%
“…It was thus concluded that the drug played a role in the efficacy of treatment by providing autonomic balance in addition to its simple effects, and for this reason, it has been reported to be safe and is not associated with severe cardiovascular diseases, although it may increase the heart rate with long-term use. In a study carried out in children to evaluate acute effects at the second hour after methylphenidate treatment, no significant difference was observed in QT, QTc and QT dispersion duration in ECG (15).…”
Section: Discussionmentioning
confidence: 95%